Gender, Geography, and Justice: Behavioral Health Needs and Mental Health Service Use Among Women in Rural Jails. (September 2021) - Comartin, Erin B.; Burgess-Proctor, Amanda; Harrison, Jennifer; Kubiak, Sheryl
This multi-jail study examines the behavioral health needs and service use in a sample of 3, 787 individuals in jail, to compare women in rural jails to their gender and geography counterparts (that is rural men, urban women, and urban men). Compared to urban women (17.9%, n = 677), rural men (18.2%, n = 690), and urban men (56.1%; n = 2, 132), rural women (7.6%, n = 288) had significantly higher odds of serious mental illness and co-occurring mental health and substance use disorders. Rural woman were nearly 30 times more likely to receive jail-based mental health services; however, a discrepancy between screened mental health need (43.1%, n = 124) and jail-identified mental health need (8.4%, n = 24) shows rural women are severely under-identified compared to their gender/geography counterparts. These findings have implications for the changing nature of jail populations and suggests the need to improve behavioral health identification methods.